O Teorema de Pitágoras Vivenciado em Laboratórios sob a Perspectiva Lúdica - Cláudia Roberta Truzi (2024)
This dissertation explores an important theorem introduced in the later years of Elementary Education and further examined in Secondary Education: the famous and fascinating Pythagorean Theorem. It is not widely known in basic education that there are over 400 proofs of this theorem. This work presents a selection of these proofs based on their affinities. The study includes both algebraic and geometric proofs and emphasizes laboratory activities developed in the classroom. It is anticipated that this study will be a valuable resource for teachers, helping to bridge the gap between students and mathematics and thereby contributing to meaningful learning. Keywords: Pythagoras, Puzzle, Challenges, Educational Games.